Optimizing mRNA delivery with targeted elastin-like polypeptide–based LENN formulations: Insights into the endocytosis mechanism - Saloni Darji; Feng Qu; Marissa Henager; Ankita Prasad; Bennett D. Elzey; Christina R. Ferreira; David H. Thompson (Proceedings of the National Academy of Sciences, 2026)
Gene delivery has emerged as a groundbreaking technique for altering gene expression, offering new possibilities in treating a vast array of diseases. We report a layer-by-layer elastin-like polypeptide nucleic acid nanoparticle (LENN) system for mRNA delivery as an attractive alternative to viral vectors and lipid nanoparticle (LNP) systems. This study focuses on determining the physical characteristics of LENN bearing mRNA cargo and assessing their biological performance in T24 bladder tumor cells. Our data show that mRNA encoding luciferase forms stable 30 to 130 nm LENN particles via batch mixing to efficiently encapsulate the mRNA strands, are resistant to heparin challenge, and are capable of storage at −20 °C for 3 d as lyophilized powders while retaining full biological activity after rehydration. We also demonstrate that LENN targeted to the epidermal growth factor receptor (EGFR) can efficiently deliver the mRNA cargo to the cytosol of EGFR+ T24 human bladder cancer cells via clathrin-mediated endocytosis where it is translationally active. Lipid profiling analyses show the significant role that upregulated phospholipid biosynthesis plays in nanoparticle internalization and endosomal escape compared to untargeted LENN, indicating the importance of the clathrin pathway in contributing to the delivery efficiency of LENN. Endocytosis inhibition experiments further support the involvement of the clathrin pathway. These findings highlight the compelling features of LENN with respect to their size, in vitro and in vivo targetability, mRNA encapsulation efficiency, complex stability, gene expression, and “green” manufacturability, offering an attractive alternative to existing methods for gene delivery.